IMPLEMENTASI OPENSID SEBAGAI MEDIA PENGEMBANGAN DIGITALISASI INFORMASI UNTUK MENINGKATKAN TRANSPARANSI PELAYANAN DESA - Abdurahman Setia; Taufik Taufik; Nur Fitrianingsih; Ita Fitriati (Universitas Citra Bangsa, 2025)
Information management in villages is one of the challenges in realizing governance that is transparent and responsive to community needs. In an effort to increase transparency and quality of services in villages, OpenSid has been implemented as a medium for digitizing information. This research aims to analyze the implementation of OpenSid in supporting the digitalization of information at the village level and its impact on transparency and public services. The research method used is a qualitative approach with a case study in one of the villages that has implemented OpenSid. Data was obtained through interviews, observation and document analysis. The research results show that the use of OpenSid is able to increase access to information and simplify the flow of village services, thereby making a positive contribution to transparency and quality of services to the community. These findings provide guidance for other villages that wish to adopt similar technology in an effort to strengthen good governance.